1996
DOI: 10.1161/01.hyp.27.2.259
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 and Its Receptor in Hypertrophic Cardiomyopathy

Abstract: Endothelin-1, a potent vasoconstrictor produced by vascular endothelial cells, activates the hypertrophic program in cultured heart muscle cells. However, the role of endothelin-1 in cardiac hypertrophy in humans is unknown. Therefore, we studied hypertrophic cardiomyopathy patients with normal pulmonary arterial pressure, in whom cardiac hypertrophy is a specific feature of the disease. Radioimmunoassay with a monoclonal antibody to human endothelin-1 showed that the plasma level of immunoreactive endothelin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 31 publications
3
34
1
Order By: Relevance
“…Furthermore, we demonstrated that inhibition of protein kinase C or Na ϩ /H ϩ exchange prevented the inotropic response to ET-1 but not to isoproterenol in human atrial trabeculae. 28 Our findings of an ET-1-induced positive inotropic effect with only minor changes in intracellular Ca 2ϩ transients are in agreement with previous reports in animal experiments in ventricular tissue. ET-1 increases contractility but does not change intracellular Ca 2ϩ transients in isolated adult ventricular myocytes from rats 4 and rabbits.…”
Section: Subcellular Mechanism Of Action Of Et-1supporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, we demonstrated that inhibition of protein kinase C or Na ϩ /H ϩ exchange prevented the inotropic response to ET-1 but not to isoproterenol in human atrial trabeculae. 28 Our findings of an ET-1-induced positive inotropic effect with only minor changes in intracellular Ca 2ϩ transients are in agreement with previous reports in animal experiments in ventricular tissue. ET-1 increases contractility but does not change intracellular Ca 2ϩ transients in isolated adult ventricular myocytes from rats 4 and rabbits.…”
Section: Subcellular Mechanism Of Action Of Et-1supporting
confidence: 93%
“…Furthermore, ET A and ET B receptors were demonstrated in human myocardium, and ET A receptor mRNA was recently found in human cardiac myocytes. 28 However, the exact characterization of the functional effects of ET-1 in nonfailing and failing human ventricles and the ET receptor subtype involved in this effect remained to be determined.…”
Section: Functional Effects Of Et-1mentioning
confidence: 99%
“…It has been previously reported that plasma neurohumoral factors, such as catecholamines 10 and endothelin-1, 11 are increased in HCM patients, but in the present study norepinephrine, but not epinephrine or endothelin-1, was increased in the HCM patients. The natriuretic peptides, especially BNP, are reported to have high predictive characteristics as a diagnostic test for heart disease 28 and we found that their concentrations were remarkably increased in the patients with HCM compared with the HHD patients and controls, which is consistent with the previous studies.…”
Section: Discussioncontrasting
confidence: 86%
“…Moreover, it has been reported that atrial natriuretic peptide (ANP) is increased in patients with hypertension. 9 With regard to HCM patients, it has been reported that plasma concentrations of catecholamines 10 and endothelin-1 11 are increased, as well as those of ANP and brain natriuretic peptide (BNP). [12][13][14][15][16] However, there are no data on the differences in the neurohumoral profiles of HCM and HHD patients.…”
mentioning
confidence: 99%
“…Calciumcalmodulin activated phosphatase-Calcineurin has been implicated in playing a major role in cardiac hypertrophy (Wilkins and Molkentin 2002). Several other growth factors, such as c-fos, c-jun, atrial and brain natriuretic peptides, and endothelin I, have been shown to be possibly involved in not only pressure overload hypertrophy but also in hypertrophy resulting from sarcomere gene mutations (Kai et al 1998;Derchi et al 1992;Hasegawa et al 1993Hasegawa et al , 1996. Adult cardiomyocytes in FHC have been shown to reactivate fetal isoforms and to down-regulate adult forms of several cardiac genes, including the cardiac myosin heavy chain gene (Komuro et al 1988;Chien et al 1993).…”
Section: Interesting Posersmentioning
confidence: 99%